Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
This issue of KIU Journal of Humanities deals with Development Administration, Social Philosophy, Gender Studies, Literary Studies, Organizational Management and Educational Management. The first part of the Journal focuses attention on Development Administration. Development Administration is concerned with development practices targeted at stimulating development in the society. It is the process of administering and organizing public agencies in order to stimulate and facilitate defined programs of social, economic progress with a purpose to make change attractive and possible. Papers in this section deal with issues in development administration such as Agenda Setting, Colonianism, the role of Women in Development Policies and so on. One of the papers in this section examines the operations and activities of the social media in enhancing agenda-setting inclusiveness within the context of a diverse and heterogeneous entity and suggests a creative synergy between the two if the country’s democratic experiment would benefit from and maximise the advantages of an all- inclusive governance. Articles in the second part of this edition center on Social Philosophy. Social philosophy as a branch of philosophy deals with social problems, especially those issues pertaining to social values. A sound social philosophy is the need of the day to tackle many a problem, which faces the society such as inequality, injustice, oppression etc. Against this backdrop, section two looks at some social philosophies such as Russell’s Philosophy of Logical Atomism, the Virtue of Moderation and Environmental Ethics, the Moral Range of Political Duty, Austin’s Speech Acts and Performative Utterances etc. and their effects on the society in order stimulate and guide basic questions on: The nature of the social world, social phenomena and social interaction (social ontology). Section Three looks into various issues in Gender Studies such as domestic violence, marital stability and sustainability, religion and women identity among others. This is because the discipline of gender studies critically examines how gender shapes our identities, our social interactions and our world. Gender studies allows people to develop a framework for thinking about power relations connected to social constructions of gender, race, class, sexuality, ability, age, and nationality through multiple perspectives and theories. Gender Studies also provides the opportunity to obtain practical tools for promotion of equity across social, political, and economic spheres. Gender Studies is diverse in that it can be applied to several other disciplines of study, like literary theory, drama studies, film studies, religious studies, performance theory, art history, anthropology, sociology, psychology, and political science. Papers in the fourth section of this edition center on Lierary Studies. Some written works of the imagination which include poetry, drama and narrative fiction were x-rayed in order to covey their wirtters’ message to the society. This is borne out of the fact that every literary work has its underlying message, or 'big idea. In other words, every literary work has a critical belief about life that the author is trying to convey in the writing of a novel, play, short story or poem. This belief, or idea, transcends cultural barriers and it is usually universal in nature. Section Five x-rays the importance of organizational management. Organizational Management is a fundamental asset to creating an environment that supports continuous improvement of individuals and their organizations to better provide for the communities they serve. Every organization needs a leader with a clear understanding of the issues facing their organization and is prepared to implement them while maintaining operational functions, developing employee skills, and managing human resources. The organizational method allows managers to break down the entire operation of a department into several phases. Dividing operational functions into sections allows management to obtain a clear picture of what the goals of a department are and how to implement the goals most effectively. It also allows managers to respond rapidly to factors that affect the internal or external expectations of company. Based on the its findings, one of the papers in this section suggests among others that participatory and charismatic leadership styles should be encouraged fully in all sectors of the economy so as to boost employees’ commitment. Papers in the last section of this edition deal with educational Management. Educational management helps in the achievement institutions’ objectives. That is, it ensures schools’ and colleges’ effectiveness. It improves interpersonal communication among members of the school or college. It is against this backdrop that one the papers in this section suggests among others that school administrators should take cognizance of the personality traits of their prospective employees before employing and redeploying them.. On the whole, this edition of KIU Journal of Humanities features many interesting, educative and informative articles which can contribute immensely to the existing knowledge on each topic.